Health-related quality of life among adolescents with type 1 diabetes since the second wave of the COVID-19 pandemic in Germany - Olga Kordonouri; Karin Lange; Juliane Regina Framme; Su-Jong Kim-Dorner; Bettina Heidtmann; Thomas Michael Kapellen; Heike Saßmann (Family Medicine and Community Health, 2023)
Objective The COVID-19 pandemic had an impact on everyday life and in general, reduced the health-related quality of life (HRQoL) of adolescents. In this study, we assess the HRQoL of adolescents with type 1 diabetes (T1D) in Germany since the second wave of the COVID-19 pandemic by using self-report and parent-proxy reports, to identify risk factors, to compare to peers and to examine the agreement of HRQoL between parents and their children.Methods A total of 445 adolescents (12–18 years) and 413 parents participated in an anonymous cross-sectional survey conducted at three German diabetes centres from January 2021 to June 2022. Inclusion criteria were diabetes duration ≥1 year and German-speaking. Teen HRQoL was assessed by using self-report and parent-proxy report versions of the KIDSCREEN-10 index.Results The majority of adolescents reported average (75.5%) HRQoL. Approximately 11.3% of teens reported high and 13.2% low HRQoL. Teen’s female gender, older age, higher diabetes burden and parental depression symptoms contributed to lower self-reported HRQoL among teens. For parent-proxy reports, increasing diabetes burdens, parental depression symptoms, non-migrant status, high education and ketoacidosis contributed to lower scores on teen HRQoL. The mean scores of the KIDSCREEN-10 index for adolescents did not differ from the German norm. In comparison to healthy peers during the first wave of the pandemic, adolescents in the current study reported higher HRQoL. The overall teen-parent agreement was fair although parents reported significantly lower teen HRQoL than adolescents did.Conclusions HRQoL of most adolescents with T1D during the COVID-19 pandemic was average with parents reporting significantly lower scores. Self-reported and parent-proxy-reported HRQoL and the level of agreement due to different perspectives can provide important information for clinical care and intervention planning.